Cadherin adhesion in the intestinal crypt regulates morphogenesis, mitogenesis, motogenesis, and metaplasia formation. Issue 4 (1st August 1999) - Perry, I; Hardy, R; Tselepis, C; Jankowski, J A
Abstract : The topographical organisation of the epithelium lining mucous membranes has been an intense point of research. One of the fundamental biological issues underpinning this and associated issues relates to the role and regulation of epithelial adhesion molecules. Adhesion between individual cells allows an intact layer to be formed, which is selectively permeable. In addition, the orchestrated regulation of multiple adhesion molecules allows the gradual transition from basal secretory cells to apical absorptive cells in the crypt-villus gradient. Moreover, it is becoming clear that no one class of adhesion molecule can sufficiently govern crypt architecture; however, the main cell-cell adhesion molecules are the cadherins and the related desmosomal cadherins. These latter molecules interact with the catenins, which bind directly or indirectly with cytoskeletal molecules such as Rho and Rac. In addition, other complex glycoproteins, such as the carcinoembryonic antigens, might contribute to adhesion, although their mechanisms of function are distinctly different. Integrins on the basal aspect of the cells also signal important morphoregulatory signals as a result of their binding to the extracellular maxtrix. The disruption of these physiological processes also provides a necessary and, in some cases, sufficient molecular mechanism for cancer invasion and metastasis, such as occurs in E-cadherin mutation positive familial gastric cancer.